The osteosynthesis of Unstable Thorax by means of Subperiostic Tiring of Plates - Barquet, Antonio; Vecsei, Vilmos (Cirugía del Uruguay, 1981)
When the usual methods of osteosynthesis are employed in multiple c'stal fractures with respiratory disfunction, they give rise to technical difficulties or lack stability with respect to fixation.